THE STABILITY AND COMPOSITION OF PHENGITIC MUSCOVITE AND ASSOCIATED PHASES FROM 5.5 TO 11 GPA: IMPLICATIONS FOR DEEPLY SUBDUCTED SEDIMENTS - Domanik K.J.; Holloway J.R. (My University, 1996)
The stability and composition of phengitic muscovite was investigated from 5.5-11 GPa, 700-1150oC in synthesis experiments performed in a multianvil apparatus. Starting materials consisted of natural minerals with a bulk composition similar to that of a K-deficient, intermediate dioctahedraltrioctahedral mica. Phengitic muscovite was found to be stable from 5.5-11 GPa at 900oC. Phengite melting occurs between 1075-1150oC at 7-8 GPa and 1000-1050oC at 10 GPa. At 10-11 GPa, 800oC octahedral cation deficient (OCD) muscovite and K-hollandite are observed rather than phengite.The average phengite content of muscovite is positively correlated with pressure ranging from 3.65 Si pfu at 5.5 GPa to 3.81 Si pfu at 11 GPa. The maximum phengite content of stable muscovite appears to be 3.80-3.85 Si pfu. Most phengite examined exhibits at least minor solid solution towards phlogopite, averaging 2.04 +/- 0.06 (2σ) octahedral cations pfu.The hydrous phases phengite, lawsonite, topaz-OH, and Mg-pumpellyite occur between 6-8 GPa, 700-900oC. With increasing pressure lawsonite and Mg-pumpellyite dehydrate to form garnet between 8-9 GPa. With increasing temperature Mg-pumpellyite, lawsonite, and topaz-OH devolatilize to form garnet and kyanite between 900-1000oC at 7-8 GPa.Phengitic muscovite and topaz-OH would be stable in hydrous sediments in cool mature subduction zones to depths exceeding 360 km while lawsonite and Mg-pumpellyite would be stable to 240-300 km allowing the transport of H2O contained in these phases deep into the upper mantle. In warmer subduction zones the dehydration of Mg-pumpellyite, lawsonite, and topaz-OH; as well as the melting of phengite would result in fluid release at depths of 180-240 km.The presence of phengite at far greater depths than the zone of melt generation beneath arcs (100-150 km) requires a mechanism such as the partitioning of K, Be, B, Ba, and Rb into migrating fluids rather than the simple dehydration of phengite beneath arcs in order to provide for the transfer of these slab signature elements from phengite into arc magmas.